Meningkatkan MENINGKATKAN KEAKTIFAN SISWA KELAS V DALAM PEMBELAJARAN PAI DENGAN METODE NUMBERED HEADS TOGETHER DI SD NEGERI SUKA RUKUN 01 - istiqomah, Rahmawati; Nurkholisoh; Wiyosa Sagita , Salsabila; Farida, Nur Aini; M. Makbul (Almarhalah: Jurnal Pendidikan Islam, 2024)
In this study, it aimed at grade V students of SD Suka Rukun 01 Bekasi Regency, the purpose of this study was to increase student activeness in class. In Islamic religious education learning, this research is a Classroom Action Research that collaborates with teachers as implementers of learning and observation as observers This Class Action Research is conducted in two cycles or two meetings. Seeing the problem in grade V SD Negeri Suka Rukun 01 is the lack of student activity in learning PAI. The activeness of the students referred to here is to have high enthusiasm and confidence in learning so that students are able to understand the material presented well. Data collection methods through observation and interviews. The data is tabulated after descriptive analysis in tabular form. Based on the results of the study, there was an increase in student activity in cycles 1 and 2 with an increase of 77.30% and 86.00% respectively. Thus, it can be concluded that the type numbered heads together cooperative method can increase the activeness of grade V students in PAI learning at SD Negeri Suka Rukun 01.